Pengelolaan Sains di Lembaga Pendidikan Islam Melalui Laboratorium - Siti Fatmawati;; Irawan Irawan; Tedi Priatna (Jurnal Dirosah Islamiyah, 2023)
The purpose of this study is to describe the management of science through laboratory utilization. This study uses a descriptive method with a qualitative approach, while the data collection technique uses observation sheets and interviews. The results of his research are that the management of the science laboratory at MA Ar-Rosyidiyyah has not been carried out properly because it has not met all the criteria included in the management tools. Of the four indicators of science laboratory management requirements include: 1). Planning 2). Organizing 3). Implementation 4). Supervision. MA Ar-Rosyidiyyah Bandung city only has 12 criteria for managing a science laboratory. Among the requirements that have not been met are the limited tools and materials that are a factor in the ineffectiveness of practicum activities in schools and the laboratory does not yet have a laboratory head or laboratory assistant so that everything is delegated to subject teachers. Keywords: Science Management, Islamic Educational Institutions, Laboratory